The Relationship Between Work Family Conflict and Performance of Female in The Workplace - Farida, Nur; Damanhuri, Damanhuri; Bahrudin, Febrian Alwan (Universitas Tanjungpura, 2024)
The objective of this study is to investigate the correlation between work-family conflict and the performance of female workers. This work employs a quantitative-correlational research methodology. This study distributed a Likert scale questionnaire through the Google Form platform as the data collection method. A correlation coefficient of 0.736 from the Rank Spearman association hypothesis test shows that there is a strong positive relationship between the work-family conflict variable and the performance of female workers. Moreover, the p-value is below 0.05 (particularly 0.037), suggesting a statistically significant association between Variable X (work-family conflict) and Variable Y (performance conflict among female workers). The motivation behind this research stems from the findings of researchers at PT. X, which indicate that married female professionals encounter challenges in balancing their household and public responsibilities.